A twist in the tale: a rare case report of asymptomatic uterine torsion in a term pregnant woman - Dev, Sushma V.; Vijay, Shilpa N.; Bhat, Mythri R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
An abnormal rotation of the uterus along its fixed longitudinal or vertical axis by a margin greater than 45 degrees is known as uterine torsion. Prenatal diagnosis is challenging, and it has multiple surgical and post-operative consequences that increase maternal and perinatal morbidity. A 33-year-old G2P1L1 with 38 weeks gestation, came with complaints of labor pains since, 2 hours was admitted in Cheluvamba Hospital, Dept of OBG, MMCRI on 7th January 2024. She was a booked case and her antenatal period was uneventful. She was taken to Emergency LSCS as she was Previous LSCS in labor. At surgery, the uterine surface was found to be covered with dilated tortuous vessels but the diagnosis of uterine torsion was unable to be made until extraction of the baby and exteriorisation of the uterus. Posterior wall uterine incision over the lower segment was performed as the uterus had rotated by 180° around its cervical junction. No uterine anomalies or fibroids were seen. Both the mother and the neonate were in good condition post operatively and were discharged from hospital 72 hours later. The degree of rotation and the stage of pregnancy determine the mother's prognosis in cases of uterine torsion. The period between 20 and 28 weeks of gestation is when the highest mortality rates occur (17%), and these rates decline with increasing gestational age. A 36% fatality rate has typically been associated with torsion of 180 to 360°. Both gestational age and the degree of torsion have an equal bearing on the fetal outcome. 71% of cases with torsion of 180 to 360° resulted in fetal death. When uterine torsion occurs unexpectedly, posterior uterine incision is a viable and time-saving procedure. A safe obstetric result is ensured by exteriorization, uterine detorsion, and careful examination of surrounding structures for injuries.